IDENTIFIKASI KEBERADAAN AIR TANAH MENGGUNAKAN METODE GEOLISTRIK RESITIVITAS KONFIGURASI SCHLUMBERGER DI DAERAH PANDAWA, JORONG TAROK, KECAMATAN 2 x 11 KAYU TANAM - Fandi Aulia Syofyan; Adree Octova; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
Pandawa, Jorong Tarok District 2 x 11 Kayu Tanam is one of the difficult areas of water in Padang Pariaman Regency. One of the causes of the difficulty to meet the water needs is due to unknown groundwater source distribution. The distribution of groundwater in Pandawa is important to know, to know the location of the water source and its subsurface shape, therefore has been conducted research that aims to know the distribution, depth, and type of ground water aquifers in the Pandawa area. This research is a descriptive basic research. Measurements were made using MAE X-612 EM Resistivitymeter as the main instrument. Data is taken using Schlumberger configuration on 3 paths. The results of data analysis are interpreted using Smoothness-Constraint Least Squares Inversion with the help of Res2dinv Software and Voxler 4.0 Software. The result of interpretation of data is the value of rock type resistance and rock depth of research area. The data estimation is done by comparing the actual type of resistance value with the species resistance table and the geology of the research area, so that the water distribution and depth of soil from the soil surface can be obtained. The results of this study indicate that the distribution of groundwater on the parallel track of Trajectory 1 and 2 tends to lead from the North to the South. Groundwater is encountered in the range from 7 - 20 m with a range of resistance values of 6.87 Ωm - 32.6 Ωm.